Debunking the myth of denial's effectiveness in crisis communication: context matters. Issue 4 (7th November 2016) - Coombs, W. Timothy; Holladay, Sherry Jean; Claeys, An-Sofie
Abstract : Purpose: The purpose of this paper is to address the under-researched issue of how formal determinations of organizational responsibility for a crisis affect the effectiveness of the denial strategy in protecting organizational reputation. Because studies that omit later determinations of responsibility produce misleading representations of the value of denial, a pilot study and primary study investigated how later determinations of organizational culpability in a management misconduct crisis interact with crisis response strategies to affect reputation and anger. Design/methodology/approach: Two studies used experimental designs to assess how denial interacted with determinations of crisis responsibility to influence reputation and anger. Findings: The pilot study demonstrated reputational damage and stakeholder anger increased when an organization initially denied responsibility and then was found to be responsible for the crisis. The second study replicated the pilot study findings and also demonstrated that later determinations of guilt decreased reputation scores. When found guilty, the organization's reputation was significantly more favorable when the positive action strategy was used. Comparison of three response strategies (no response, denial, and positive action) revealed the denial and no response conditions were significantly less effective than the positive response strategy when the organization was found guilty. Research limitations/implications: Paper demonstrates the need for research on the denial strategy to consider later determinations of crisis responsibility (guilt) when assessing denial's impact on organizational reputation. Practical implications: When selecting response strategies in situations where crisis responsibility is unclear, practitioners should consider how later determinations of responsibility could affect reputation. Originality/value: This paper questions past research on the value of the denial strategy, integrates findings from the trust violations research, and demonstrates the importance of considering formal judgments of organizational responsibility when selecting crisis response strategies.